PENGEMBANGAN SUMBER DAYA MANUSIA DI INDONESIA MELALUI PENDIDIKAN ISLAM - Assidiqi, Muhammad Hasby; Irnie Victorynie (LPPM STAI Muhammadiyah Probolinggo, 2025)
Human resource development (HRD) is a program aimed at improving individual quality through education. Therefore, it is important for Indonesia to implement effective educational approaches, focusing on creativity and innovation while also applying education based on religion and Pancasila. Education in Indonesia needs to be supported by policies that enhance quality, such as the possibility of reinstating national exams after a four-year absence. Changes in the education system are crucial for fostering innovation and creativity. Education should be engaging and enjoyable, with teachers who continuously learn to provide positive learning experiences for students. Islam, as a religion that emphasizes education, teaches the importance of early education to shape a quality generation. The research method used in this analysis is descriptive or documentation study, aimed at illustrating how Islamic education can contribute to HR development. The findings indicate that quality education is key to enhancing individuals' contributions to society. Islamic Religious Education (PAI) in Indonesia is based on Pancasila values, emphasizing belief in God as a moral guide. Thus, education serves as a means to build and develop students' character and personality while creating a supportive community for goodness and truth.